Prenatal Exposure to Paint Thinner Alters Postnatal Development and Behavior in Mice - Malloul, Hanaa; Mahdani, Ferdaousse M.; Bennis, Mohammed; Ba-M’hamed, Saadia (Frontiers in Behavioral Neuroscience, 2017)
Occupational exposure and sniffing of volatile organic solvents continue to be a worldwide health problem, raising the risk for teratogenic sequelae of maternal inhalant abuse. Real life exposures usually involve simultaneous exposures to multiple solvents, and almost all the abused solvents contain a mixture of two or more different volatile compounds. However, several studies examined the teratogenicity due to industrial exposure to a single volatile solvent but investigating the teratogenic potential of complex chemical mixture such as thinner remains unexplored. This study was undertaken to evaluate developmental neurotoxicity of paint thinner using a mouse model. Mated female mice (N=21) were, therefore, exposed to repeated and brief inhalation episodes of 0, 300 or 600 ppm of thinner during the entire period of pregnancy. Females weigh was recorded and their standard fertility and reproductive parameters were assessed. After birth (PND1), offspring (N=88) length and body weight were measured in a daily basis. At PND5, the pups were assessed for their postnatal growth, physical maturation, reflex development, neuromotor abilities, sensory function, activity level, anxiety, depression, learning and memory functions. At adulthood, structural changes of the hippocampus were examined by estimating the total volume of the dentate gyrus. Except one case of thinner induced abortion at the higher dose, our results showed that the prenatal exposure to the solvent did not cause any maternal toxicity or decrease in the viability of the offspring. Therefore, a lower birth weight, decrease in the litter size and delayed reflexes ontogeny were registered in prenatally exposed offspring to both 300 ppm and 600 ppm of thinner. In addition, prenatally exposure to thinner resulted in increased anxiolytic- and depression-like behaviors. In contrast, impaired learning and memory functions and decreased hippocampal dentate gyrus volume were revealed only in the prenatally treated offspring by 600 ppm of thinner. Based on these results, we can conclude that prenatally exposure to paint thinner causes a long-lasting developmental neurotoxicity and alters a wide range of behavioral functions in mice. This shows the risk that mothers who abuse thinner paint expose their offspring.